Contribution of parental blood pressures to association between low birth weight and adult high blood pressure: cross sectional study - Walker, Brian R (British Medical Journal, 1998)
Objective: To examine the possibility that low birth weight is a feature of the inherited predisposition to high blood pressure. Design: Cross sectional study. Setting: Primary care medical centre in Edinburgh. Subjects: One offspring of 452 families (231 men and 221 women aged 16-26 years) in whom blood pressure, weight, and height were measured in 1986 and whose parents had blood pressure measured in 1979. Birth weights were obtained from case records (270 offspring) or by questionnaires sent to the mothers (182 offspring). Main outcome measures: Birth weight and adult systolic blood pressure in offspring in relation to parental blood pressure. Results: If parental blood pressures were not considered, a 1 kg decrease in birth weight was associated with a 2.24 mm Hg increase in systolic blood pressure of offspring (P=0.06) after correction for current weight and sex. However, parental blood pressures correlated positively with blood pressure of offspring, and higher maternal blood pressure was associated with lower birth weight (−3.03 g/mm Hg, P<0.01). After correction for parental blood pressures, a 1 kg decrease in birth weight was associated with only a 1.71 mm Hg increase in the systolic blood pressure of the offspring (P=0.15). Conclusions: Low birth weight is a feature of the inherited predisposition to hypertension, perhaps because it is associated with higher maternal blood pressure during pregnancy. Parental blood pressure may be an important confounding factor in the relation between low birth weight and subsequent hypertension.